A chorus of voices: the voice as an identity marker - Blanco Fuente, Irene (Comunicación y Género [Communication and Gender], 2020)
This article explores how the voice hold a wealth of information for analysing identity and power relations despite the fact that it has not been sufficiently taken into account in an academic context. By means of working from the established and rational idea of the voice in the western tradition, this reflection offers an approach to the physical demonstration of the voice. From this established base, we will then move to exploring a historical vision of the voice in relation to gender. To fully consider this, the theoretical concept of intersectionality proves useful in today’s society to fully include a diverse range of voices. In addition, this research assesses how technology takes part in voice perception and the way voices are being constructed for technological devices.
Keywords: voice; identity; power; recognition